Production of highly enantioselective (-)-menthyl butyrate using Candida rugosa lipase immobilized on epoxy-activated supports - Othman S.S.; Basri M.; Hussein M.Z.; Abdul Rahman M.B.; Rahman R.N.Z.Abd.; Salleh A.B.; Jasmani H. (2024)
Optically active (-)-menthyl butyrate was synthesized by enantioselective esterification of racemic (±)-menthol and butyric anhydride using lipase from Candida rugosa immobilized onto epoxy-activated supports of Eupergit C and Eupergit C 250 L through physical adsorption method. The effects of various temperature, storage condition, stability in organic solvent and lipase recyclability were investigated for their influence on the enzymatic enantioselective formation of (-)-menthyl butyrate. The immobilized lipases retained high catalytic activity of up to 31% yield and 100% enantiomeric excess of the desired product, and showed better stability compared to the native lipase. They also exhibited about 50% retained activity even after incubation at higher temperatures, storage at room temperature and after long incubation in hexane. Immobilized lipases also showed considerably efficient reusability.